Some thoughts about technology management - Quy, Le Minh; Doanh, Hoang Ngoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Technology management plays a very important role in the process of production and realization of the scientific and technological development based industrialization and modernization of the country. Experience of other newly industrialized countries (NICs) shows that in order to built an economic structure and a modern production based on the development of science and technology (S&T) it should improve the technological level of production. To do that it should improve the efficiency of technological administration and management. This paper discusses basic issues related to technology management. Code: 13092501 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">